A Preliminary Study of Cobalt Solvent Extraction from Nickel Sulphate Solution Using Organic Extractant-PC-88A - Subagja, Rudi; Rohman, Arief Dwi; Milandia, Anistasia; Oediyani, Soesaptri; Setiawan, Iwan (National Research and Innovation Agency (BRIN), 2023)
In present study, a solvent extraction experiment has been done to separate cobalt from the nickel sulfate solution by using 2-ethythexyl phosponic acid mono-2-ethylhexyl ester (PC-88A) as extractant. The experiment was carried out on a laboratory scale by using a separating funnel to extract cobalt from the nickel sulfate solution with PC88A. The mixed solution was shake in separating funnel for a specified period of time, and after the solvent extraction experiment was finished the organic phase PC88 was separated from the nickel sulfate solution by decantation. The nickel and cobalt content in the aqueous nickel sulfate solution were then analyzed using Atomic absorption spectrophotometry (AAS). In this experiment, the variable for experiments were covering solution pH from 2 to 6, shaking time from 30 minutes to 120 minutes, shaking speed from 20 revolutions per minute (rpm) to 80 rpm, and the volumeratio of aqueous to organic phase (A:O ratio) was from 1:1 to 1:4. The effects that experimental variables to the cobalt extraction were observed in this experiment. The result of experiment at room temperature, solution pH 5, shaking speed 60 rpm, shaking time 90 minutes, A:O ratio 1:4 and concentration of PC- 88A 40% show 97.21% of cobalt can be extracted by PC-88A from nickel sulfate solution, thererfore it was necessary to conduct two stage extraction process to extract 100% of the cobalt from the nickel sulfate solution.